Stability Studies of Over the Counter Quaternary Mixture Containing Phenylephrine Hydrochloride, Chlorpheniramine Maleate, Paracetamol and Caffeine Using Different Chromatographic Methods. Issue 3 (4th May 2018) - Ragab, Marwa A.A.; El Yazbi, Fawzy A.; Hassan, Ekram M.; Khamis, Essam F.; Hamdy, Mohamed M.A.
Abstract: An over the counter quaternary drugs mixture for treatment of common cold was analyzed using a stability-indicating HPLC and HPTLC methods with two different mobile phases. The mixture composed of phenylephrine hydrochloride (PHE), chlorpheniramine maleate (CPM), paracetamol (PAR) and caffeine (CAF) and it was successfully analyzed in bulk drug and in its dosage form. For the achievement of effective HPLC separation and analysis, Agilent 5 HC-C18 (2) 150 x 4.6 mm was used with a mobile phase system comprising of 20 mM phosphate buffer pH 3 along with both acetonitrile and methanol in a gradient elution mode. The cited drugs were resolved with retention times 2.01, 3.01, 4.71 and 9.61 min for PHE, PAR, CAF and CPM, respectively. Different stress conditions were carried out on the drugs and their yielded forced degradation products were entirely resolved from the parent drugs. The separation done using the HPTLC method was achieved using two different mobile phases. Chloroform-methanol-ammonia (9: 1: 0.1, v / v ) (mobile 1) and ethyl acetate-acetone-ammonia (6.5: 3.5: 0.1, v / v ) (mobile 2) were used as mobile phase systems.